Efficacy of Lumbrokinase and Warfarin Compared to Single Warfarin on Thrombus Resolution in Deep Vein Thrombosis - Anggia Endah Satuti; Hariadi Hariawan; Hasanah Mumpuni (ACI (Acta Cardiologia Indonesiana), 2015)
Background: Deep vein thrombosis (DVT) is a challenging condition for clinician in all specialities. Prognosis after vein thromboembolism is worse and much worse after pulmonary embolism. Anticoagulant is the mainstay therapy for deep vein thrombosis, but there is still slow thrombus resolution even with the use of optimal anticoagulant. The use of intravenous thrombolytic agentsis one of the methods to signifi cantly lyse thrombus. Since there is increasing risk of bleeding with the use of the agents, indication is limited. Lumbrokinase is oral thrombolytic that may give significant thrombus lyses without increasing the risk of bleeding for deep vein thrombosis. This study was conducted to compare single warfarin therapy with combination of lumbrokinase andwarfarin for thrombus resolution in deep vein thrombosis patients. Methods: This study was a randomized open labeled trial comparing deep vein thrombosis patients using single warfarin therapy group to group using combination lumbrokinase and warfarin. 22 patients meet the inclusion and exclusion criteria. Patients were followed for 30 days and in the end of the trial, evaluation using vascular Doppler ultrasonography was done. Chi-square analysis was used to compare the outcome between two therapy groups. Results: In this trial, group therapy with added lumbrokinase to warfarin yielded a tendency toward better thrombus resolution compared to group with single warfarin therapy (58.3% vs.30%, p=0.231). Conclusion : Added therapy with lumbrokinase to warfarin may give better thrombus resolution as compared to single warfarin therapy, although there is no signifi cant difference between groups.Keywords: deep vein thrombosis, lumbrokinase, warfarin